The Effect of Cinnamon (Cinnamomum burmanii) Aqueous Extract on Pancreas Structure of Diabetic Mice (Mus musculus) Strain Balb-C - Ika Dewi Kusumaningtyas; Susantin Fajariyah; Eva Tyas Utami (Jurnal ILMU DASAR, 2014)
The objectives of this study were to observe effect and  the effective dose of cinnamon (Cinnamomum burmanii) aqueous extract on pancreas structure of strain Balb-C mice (Mus musculus) diabetic after alloxan exposure. A total of 30 strains Balb-C mice (Mus musculus L.) were divided into 5 groups. Negative control group was not induced  by alloxan and a positive control group was induced alloxan 0,15 mg/g bw intraperitoneally for 9 days. The treatment group was divided into 3 groups was induced alloxan 0,15 mg/g bw and given an aqueous  extract of cinnamon at a dose of 0,73 mg/g bw; 1,09 mg/g bw and 1,45 mg/g bw orally for 7 days. Mice were dissected pancreas histhological taken using paraffin method and Haematoxylin-eosin (HE) stain. The result showed giving aqueous extract of cinnamon gave a strong effect in the repairing of pancreas structure after giving the alloxsan and the most effective aqueouse xtract of cinnamon with dose of 0,73 mg/g bb was able to repair the structure of mice's pancreas after giving the alloxan. Keywords: Cinnamon,  pancreas structur,diabetic mice